PENGARUH KEPUASAN KERJA, BUDAYA ORGANISASI DAN QUALITY OF WORK LIFE TERHADAP EMPLOYEE ENGAGEMENT (KETERIKATAN KARYAWAN) DIVISI NON PRODUKSI PT. TEJA SEKAWAN GROUP - Novita Dwi Indriyani; Rizka Novianty Haninda; Yudita Enimasariang Lombu (Fakultas Ekonomi Universitas Yos Soedarso, 2019)
Employee engagement has become one of the most popular issues today. In the study of human resource management, this has become popular because employee engagement provides many benefits for the company. The more employees feel bound to the company, the more creative and enthusiastic employees will feel so that they feel enthusiastic about working and exert all their abilities to achieve company goals. The formulation of the problem in this study is to determine whether job satisfaction, organizational culture and quality of work life will have an influence on employee engagement (employee engagement) at PT. Teja Sekawan Group . And the purpose of this study was to determine the effect of each variable job satisfaction, organizational culture and quality of work life on the variable employee engagement (employee engagement) at PT. Teja Sekawan Group . The research data were collected using observation and questionnaire methods, using a saturated sample of 51 respondents from all non-production or office employees at PT. Teja Sekawan Group . The data analysis technique used is multiple linear regression analysis to prove the research hypothesis. The data that has met the validity, reliability, and classical assumption tests are then processed to obtain a regression equation. Based on the results of research and discussion, it can be concluded that each variable of job satisfaction, organizational culture and quality of work life has a positive and significant effect on the variable employee engagement (employee engagement) at PT. Teja Sekawan Group . Keywords: Job Satisfaction; Organizational culture; Quality Of Work Life; Employee Engagement (Employee Engagement).